Development design study of heart rate, spo2, and temperature measurement of infant using non-invasive infawrap device - Mohd Hanafi, Abdul Rahim (2022)
Non-invasive treatments are a conservative treatment option that should be considered to treat patients and infants without causing pain and provide them with better outcomes than their invasive counterparts. In light of the advantages of the former, in this study, the physiological parameters of the infants were measured using a non-invasive device called the InfaWrap. The previous development of InfaWrap needs improvement in a variety of aspects such as size, weight, usability, and functionality depending on user requirement. Thus, a quantitative method design based on an iterative methodology was used to evaluate the usability of the InfaWrap device by end-users. In this study, the usability questionnaire was developed and applied with focus groups involving health professionals and parents. Furthermore, the design analysis, impact/fall testing, and measurement accuracy testing were carried out to determine the structural soundness and reliability of the InfaWrap device. Besides that, the InfaWrap device was used to assess the accuracy of heart rate, SpO2, and actual patient-specific body temperature. Owing to varying user requirements, we made design revisions and added IoT functionality. The InfaWrap device is currently smaller and lighter for infants. Meanwhile, the drop test results for both the flat drop test and the edge drop test with a height of 1 meter indicated that the device still functions for both specimens. On the negative side, several materials such as screw hole, casing and LCD screen was broken particularly for dummy specimens. The dummy InfaWrap casing shows visible cracks and scratches due to the falling impact force produced during multiple simulated tests. In the design analysis, the InfaWrap device can be accepted a maximum stress of 4.138 MPa when a force of 12 N is applied. According to the results of the accuracy test, the sensors are reliable and accurate when measuring the vital signs of an individual. The heart rate, SpO2, and temperature readings acquired with InfaWrap indicated that InfaWrap was accurate for all three parameters in both legs. The medical professionals and parents who participated in this study believed that InfaWrap helps them keep an eye on their infants more effectively. Patient SpO2 and temperature are the most accurate representations of normal and healthy state according to the validated patient heart rate and SpO2 values. The parameter values for heart rate and SpO2 precision using a real patient-specific InfaWrap are still within the normal range. Consequently, the results, based on hospital data reference, demonstrated that InfaWrap gives accurate readings to be used in hospital or home.